Synthesis, Characterization, In Silico And In Vitro Evaluations Of Benzimidazolium Derived N-heterocyclic Carbenes And Their Silver (I)-nhc Complexes - Zin, Nor Farah Hani Md (2023)
Two new series of asymmetrical benzimidazolium-based N-heterocyclic carbene (NHC) ligands and their Ag(I)-NHC complexes were synthesised and characterised using Fourier-transform infrared (FTIR) and Fourier-transform nuclear magnetic resonance (FT-NMR) spectroscopies and CHN elemental analysis. The ligands, 1-13 were synthesized via alkylation of 1-methyl/octadecylbenzimidazole with alkyl bromides (C = 4-18 in even parity), These ligands were reacted with silver oxide (Ag2O) via in situ deprotonation reaction, followed by metathesis reaction with potassium hexafluorophosphate (KPF6) to yield Ag(I)-NHC complexes, 14-25. The binding free energies (ΔG), inhibition constants (Ki) and the interactions of ligands 1-13 and selenoenzyme thioredoxin reductase (TrxR) were predicted using molecular docking. The in vitro cytotoxicity of all compounds, 1-25 against human cervical cancer cells (HeLa) and human skin fibroblasts (Hs27) were evaluated using the MTT assay. The length of alkyl chains on nitrogen atoms in the benzimidazolium moiety, as well as the presence of Ag+ ions, influenced the cytotoxicity of these compounds. Cytotoxicity of these compounds increased with increasing alkyl chain length. For ligands, the long-chain homologues, 9-11 (C10-C14) were more potent (IC50 = 1.35-12.68 μM) and selective than the short-chain analogues, 1-4 (IC50 = 3.53-35 μM) against HeLa cells.